Antibacterial Activities, Phytochemical Screening and Metal Analysis of Medicinal Plants: Traditional Recipes Used against Diarrhea - Nasir Mahmood; Ruqia Nazir; Muslim Khan; Abdul Khaliq; Mohammad Adnan; Mohib Ullah; Hongyi Yang (MDPI AG, 2019)
The aim of this study was to explore the phytochemical composition, heavy metals analysis and the antibacterial activity of six medicinal plants i.e., Terminalia chebula Retz (fruits), Aegle marmelos L., (fruits), Curcuma longa L., (rhizomes), Syzygium aromaticum L., (flower buds), Piper nigrum L., (seeds), Cinnamomum cassia L., (barks) and its two remedial recipes (recipe 1 and 2) used against diarrhea obtained from the local herbal practitioners (Hakeems). A preliminary phytochemical screening of the above-mentioned plants extract in methanol, chloroform, n-hexane and distilled water revealed the presence of various constituents such as alkaloids, flavonoids, tannins and saponins by using standard procedures. The quantitative phytochemical studies shows that alkaloids, flavonoid and saponins were in maximum amount in Terminalia chebula. The concentration of Cd, Ni, Pb, Fe, Cr, Cu and Zn were investigated by using an atomic absorption spectrometer. The obtained analysis shows that Cr, Fe and Pb were present in the highest concentration in medicinal plants and their recipes. The antibacterial activities of the crude extract found in the recipes of methanol, chloroform, n-hexane and distilled water were analyzed by using agar well disc diffusion assay and minimum inhibitory concentration (MIC) by broth dilution method against four bacterial strains, namely, E. coli, Salmonella, Shigella and Methicillin-resistant Staphylococcus aureus (MRSA), respectively. The maximum zones of inhibition in methanol, water, chloroform and n-hexane extracts were seen in recipe 2 against Shigella (22.16 ± 0.47 mm), recipe 2 against Shigella (20.33 ± 0.24 mm), recipe 1 against Shigella (20.30 ± 0.29 mm) and recipe 2 against E. coli (30.23 ± 0.12 mm), respectively. Furthermore, the recipe extracts are more active against the tested bacterial strains than the extracts from individual plants. Therefore, it is concluded that the use of herbal plants and their recipes are the major source of drugs in a traditional medicinal system to cure different diseases.